The Need for Internet Protocol Security in Data Communication - Dr. Umoh. Mfreke E.; Thursday Sunday D. (International Journal on Human-Computing Studies, 2022)
In the 21stt century with the rapid development in technology, many organizations depend on ICT for reliability and security of information to increase their performance and productivity. Internet Protocol Security (IPsec) is a suite of protocols and services that provide security for IP networks. It is a widely used virtual private network (VPN) technology. Early TCP/IP development did very little for ensuring the security of communication between peering devices. As networks evolved so did the need for greater protection of the data transmitted. IP packets lack effective security mechanisms and may be forged, stolen, or tampered with when being transmitted on an insecure public network, such as the Internet. Solutions for data protection were developed from which IPSec emerged as security architecture for the implementations of data confidentiality, integrity and availability. This paper is designed to give one the knowledge and skills to identify, mitigate and prevent malicious intrusion from the internet and guard against attackers.